IL-25 and IL-25 Receptor Expression on Eosinophils from Subjects with Allergic Asthma - Tang, Wei; Smith, Steven G.; Beaudin, Sue; Dua, Benny; Howie, Karen; Gauvreau, Gail; O'Byrne, Paul M. (International archives of allergy and immunology, 2014)
Background: Allergic asthma is an inflammatory airway disease in which Th2 cytokines play an important role. Epithelial-derived interleukin (IL)-25 has been suggested to be important in the maintenance of Th2-type responses. The effects of IL-25 are mediated by the IL-25 receptor, composed of two subunits, IL-17RA and IL-17RB. Eosinophils are effector cells in allergic asthma. The role of IL-25 in eosinophil function is unknown. This study examined the expression of IL-25 and its receptor on eosinophils in allergic asthmatics compared to atopic nonasthmatics and normal controls. Methods: The expression of IL-25, IL-17RA and IL-17RB on eosinophils, and levels of plasma IL-25 were measured in 14 normal control subjects, 15 atopic nonasthmatics and 14 mild allergic asthmatics. Results: The expression of IL-17RB on eosinophils was significantly higher in allergic asthmatics (43.08%, range 33.96-59.98%) than in atopic nonasthmatics (11.98%, range 6.33-27.11%, p = 0.002) and normal controls (17.70%, range 10.97-38.9%, p = 0.01). IL-17RA expression was also significantly higher in the allergic asthmatic group. No differences were observed in the intracellular expression of IL-25. The concentration of IL-25 in plasma was significantly increased in the allergic asthmatics (145 ng/ml, range 64-290 ng/ml) when compared to the normal controls (21 ng/ml, range 0-116 ng/ml, p = 0.012), but not compared to atopic nonasthmatics. There was a significant negative correlation between FEV 1 % predicted and the IL-25 level in the plasma (r = -0.443, p = 0.003). Conclusions: The increased IL-25 levels in plasma and the expression of IL-17RA and IL-17RB on eosinophils in allergic asthma patients suggests that IL-25 may activate eosinophils during allergic inflammation.